1986
DOI: 10.1530/jrf.0.0760267
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic and morphological characteristics of granulosa and thecal compartments of the differentiating rabbit corpus luteum in culture

Abstract: On the day after ovulation, the thecal tissue and associated mural granulosa lutein cells of the rabbit corpus luteum were separated from the granulosa lutein 'core' by dissection and these tissues were cultured separately or together (whole corpus luteum) in defined medium for 10 days on stainless-steel grids. The medium was changed completely every 24 h. Replicate tissues were cultured with testosterone (10 ng/ml), but no other hormones were added to the medium. Progesterone production increased during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Lipid droplets in the CL or cultured luteal cells have been identified by using electron microscopy for several species including humans, rats, rabbits, cows and sheep (Blanchette, 1966;Enders, 1973;Schmidt et al, 1984;O'Shea et al, 1986O'Shea et al, , 1989Yuh et al, 1986;Fields et al, 1992;Fields and Fields, 1996;Towns et al, 1999). In our study, we not only identified presence and localization of LDs in LLC and SLC but we also quantified LDs demonstrating that the mean and median volume of individual LD was greater in SLC than LLC.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid droplets in the CL or cultured luteal cells have been identified by using electron microscopy for several species including humans, rats, rabbits, cows and sheep (Blanchette, 1966;Enders, 1973;Schmidt et al, 1984;O'Shea et al, 1986O'Shea et al, , 1989Yuh et al, 1986;Fields et al, 1992;Fields and Fields, 1996;Towns et al, 1999). In our study, we not only identified presence and localization of LDs in LLC and SLC but we also quantified LDs demonstrating that the mean and median volume of individual LD was greater in SLC than LLC.…”
Section: Discussionmentioning
confidence: 99%
“…Since growth factors, which are also effective in angiogenesis, stimulate prostaglandin biosynthesis (15), it could very well be that luteal prostaglandins are important factors for the regulation of blood flow in the corpus luteum. Studies with whole corpora lutea in culture (26) or perfusion technology could help to resolve this important issue in better understanding regulation of luteal function arid ovarian blood flow.…”
Section: Discussionmentioning
confidence: 99%